Fatores associados ao absenteísmo-doença de trabalhadores da saúde hospitalares - Paiva, Larissa Garcia de (2019)
The conceptions of work are currently influenced by economic, social and cultural contexts, leading to a need to understand the role played by work in the health-illness process, given its influence on workers' lives. Health workers, in this context, are among the most prone to illness and consequent abstention from work, due to a number of associated factors. Thus, this study aimed to investigate factors associated with absenteeism-illness of hospital workers with the following guiding question: “What are the factors associated with absenteeism-disease of health workers in a hospital environment, the profile and index of these leaves as well as the impact on health costs? ”. This is a quantitative, observational study based on data from the Occupational Health and Work Safety Service of the University Hospital of Santa Maria. This study included 559 health workers from the Brazilian Company of Hospital Services, admitted from September 2014 and who had completed at least one (1) year of activity in the referred hospital. Sociodemographic, labor, health and admission and periodic laboratory tests were collected. Statistical analysis was performed using descriptive analysis, T test, WilCoxon, Qui2 and logistic regression. The results showed a sickness absence rate of 2.01% in the first year after admission and 2.32% in the 4-year period, with a cost of R $ 2,328,498.26 in four years. There was also an increase in erythrocyte, MCV, HCM, RDW, eosinophil, cholesterol and HDL values within one year of admission. Red blood cells increase the risk of withdrawal by 1.96 times (95% CI = 1.28 - 3.01); triglycerides reduce the risk by 0.66 (95% CI = 0.41 - 1.07) and LDL reduce the risk by 0.65 times (95% CI = 0.43 - 1.00). Thus, it is concluded that, in order to achieve a complete state of health in both personal and working life, it is necessary to understand not only the social, economic, organizational but also individual determinants of each worker, responsible for the quality of work. their life and health. Actions to promote health and prevent the quality of life of workers should have as their main objective changes in work processes that include work-health relationships in all their dimensions. Therefore, the main contribution of this work is to provide subsidies for prevention and health promotion actions of these workers as well as reduction in health expenses resulting from their leaves, serving as a simple screening test from known data that could change the prognosis and absence rate without adding costs to the health care system.